Ta có : \(x=7\Rightarrow x+1=8\)
\(B=x^{15}-\left(x+1\right)x^{14}+\left(x+1\right)^{13}-\left(x+1\right)x^{12}+...+\left(x+1\right)x-x+2\)
\(=x^{15}-x^{15}-x^{14}+x^{14}+x^{13}-x^{13}-x^{12}+...+x^2+x-x+2=2\)
Vì x=8=>x+1=8 thay vào B ,Ta có:
B = x15 - 8x14 + 8x13 - 8x12 + ... - 8x2 + 8x – 5 với x = 7
=x15-(x+1)x14 +(x+1)x13-(x+1)x12+...-(x+1)x2+(x+1)x-5
=x15-x15-x14+x14+...-x3-x2+x2+x-5
=x-5
Thay x=7 ,ta đc:
7-5=2
Vậy B=2
x = 7 => 8 = x + 1
Thế vào B ta được
B = x15 - ( x + 1 )x14 + ( x + 1 )x13 - ( x + 1 )x12 - ... - ( x + 1 )x2 + ( x + 1 )x - 5
B = x15 - ( x15 + x14 ) + ( x14 + x13 ) - ( x13 + x12 ) - ... - ( x3 + x2 ) + ( x2 + x ) - 5
B = x15 - x15 - x14 + x14 + x13 - x13 - x12 + ... - x3 - x2 + x2 + x - 5
B = x - 5
B = 7 - 5 = 2
1. Tính giá trị :
\(B=x^{15}-8x^{14}+8x^{13}-8x^{12}+...-8x^2+8x-5\)
\(=x^{15}-7x^{14}-x^{14}+7x^{13}+x^{13}-7x^{12}-...-x^2+7x+x-5\)
\(=x^{14}\left(x-7\right)-x^{13}\left(x-7\right)+x^{12}\left(x-7\right)-...-x\left(x-7\right)+x-5\)
\(=\left(x^{14}-x^{13}+x^{12}-...-x\right).\left(x-7\right)+x-5\)
Thay x = 7 vào biểu thức trên , ta có :
\(B=\left(7^{14}-7^{13}+7^{12}-...-7\right)\left(7-7\right)+7-5\)
\(=\left(7^{14}-7^{13}+7^{12}-..-7\right).0+7-5\)
\(=0+7-5\)
\(=2\)
Vậy biểu thức B = 2 khi x = 7 .
Học tốt